CORPORATE STRATEGIES IN GOVERNANCE AND TAX PLANNING: ANALYSIS OF NIGERIA’S PHARMACEUTICAL INDUSTRY - Okorie, Michael Chinedu; Adebowale, Elizabeth Ngozi (International Research Journal of Arts and Communication, 2024)
Corporate governance is essential for the efficient and effective management of resources by firms to achieve their desired goals. Taxes are a significant source of revenue for any country, and tax planning is crucial to minimize the tax burden and maximize shareholders' profits. This study seeks to investigate whether corporate governance mechanisms have an impact on corporate tax planning in Nigeria. Previous studies on corporate governance and tax planning have shown conflicting arguments, necessitating further investigation. This paper examines the relationship between corporate governance mechanisms and tax planning practices to minimize tax liability. The study adopts a qualitative research methodology, using data from interviews with top managers from various Nigerian firms. The study identifies corporate governance mechanisms such as board size, managerial ownership, board independence, executive compensation, board diversity, audit committee size and independence, amongst others that impact corporate tax planning. The findings reveal that corporate governance mechanisms impact tax planning practices, and firms with effective governance structures can develop tax planning strategies that minimize their tax liabilities while maximizing shareholder profits. This study contributes to the literature on corporate governance and tax planning and has important implications for policymakers, managers, and stakeholders, particularly in emerging economies.